2014
DOI: 10.15241/lwm.4.5.481
|View full text |Cite
|
Sign up to set email alerts
|

School Counselors’ Perceptions of Competency in Career Counseling

Abstract: School counselors are a well-positioned resource to reach the significant number of children and adolescents with mental health problems. In this special school counseling issue of The Professional Counselor, some articles focus on systemic, top-down advocacy efforts as the point of intervention for addressing child and adolescent mental health. Other articles investigate improving child and adolescent mental health through a localized, groundlevel approach by developing school counselors' competency areas and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 30 publications
2
26
0
Order By: Relevance
“…The results from these studies indicated that career and college counseling services and the frequency and quality of meetings with school counselors were significant factors in postsecondary planning and success, respectively. In a qualitative study, Morgan et al (2014) examined nine school counselors’ perceptions of their ability to provide career counseling. On the basis of specific themes identified in the study (i.e., challenges to delivery, opportunity, self‐doubt, reliance on colleagues, and the use of technology), Morgan and colleagues concluded that the school counselors felt incompetent about their ability to provide career counseling services.…”
Section: Self‐efficacy For Enhancing Career and College Readinessmentioning
confidence: 99%
See 1 more Smart Citation
“…The results from these studies indicated that career and college counseling services and the frequency and quality of meetings with school counselors were significant factors in postsecondary planning and success, respectively. In a qualitative study, Morgan et al (2014) examined nine school counselors’ perceptions of their ability to provide career counseling. On the basis of specific themes identified in the study (i.e., challenges to delivery, opportunity, self‐doubt, reliance on colleagues, and the use of technology), Morgan and colleagues concluded that the school counselors felt incompetent about their ability to provide career counseling services.…”
Section: Self‐efficacy For Enhancing Career and College Readinessmentioning
confidence: 99%
“…Given the potential gap between counselor preparation and the importance of being prepared, many school counselors may not feel efficacious in delivering or developing career and college programming (Clinedinst & Koranteng, 2017; Morgan, Greenwaldt, & Gosselin, 2014). Consequently, the purpose of the present study was to assess career and college readiness self‐efficacy of a sample of school counselors across regions, professional settings, and levels of training to attempt to locate where the challenges are (e.g., geographic locations, types of schools, training) and provide recommendations for closing the gap between readiness and expectations nationally.…”
mentioning
confidence: 99%
“…Career guidance interventions at the elementary school level can be offered in a variety of forms, including both traditional classroom-based instruction and web-based instruction. Additionally, technology-based career development programs appear to be used more often by counselors than other types of counseling tools (Morgan, Greenwaldt, & Gosselin, 2014). Additionally, technology-based career development programs appear to be used more often by counselors than other types of counseling tools (Morgan, Greenwaldt, & Gosselin, 2014).…”
Section: Career Guidance Interventionsmentioning
confidence: 99%
“…With the surge in popularity of online instruction, more children are engaged in virtual learning experiences than ever before (Madden, Ford, Miller, & Levy, 2006). Additionally, technology-based career development programs appear to be used more often by counselors than other types of counseling tools (Morgan, Greenwaldt, & Gosselin, 2014). However, it is important to recognize that although some literature exists regarding the value of integrating technology into career counseling (Harris-Bowlsbey, 2013;Harris-Bowlsbey & Sampson, 2001), much of it focuses on young and middle-aged adults and excludes children.…”
Section: Career Guidance Interventionsmentioning
confidence: 99%
“…In this regard, the extent to which school counselors are satisfied and whether there are positive expectations for the future may be related to how well they feel professionally enough. Considering the information provided in the related literature, it has been observed that number of studies in Turkey and in rest of the world regarding counseling self-efficacy are limited (Chandler, Balkin andPerepiczka, 2011, Sour, Ismuk andBright, 2015;Lent et al, 2006 Morgan, Greenwaldt andGosselin, 2014). It is thought that there is a need for studies in which the counseling self-efficacy of school counselors is assessed.…”
Section: Introductionmentioning
confidence: 99%